The Effect of Perception of Religious Education Curriculum Changes on the Learning Motivation of Students at the AL ISLAM Tenggulun Solokuro Lamongan Islamic Boarding School - Yogi Muhammad Saputro; Arif Muhammad; Afif Afandi; Benny Prasetya (CV Kalimasada Group, 2026)
Purpose - This study aims to analyze the influence of perception of changes in the religious education curriculum on the learning motivation of students at the Al-Islam Islamic Boarding School Tenggulun Solokuro Lamongan. The background of this research departs from the reform of the pesantren curriculum that combines salafiyah approaches and modern education to make it more relevant to the needs of the 21st century. Design/Methodology/Approach - This study uses an explanatory quantitative method with a sample of 100 students selected through purposive sampling techniques. The research instrument was in the form of a Likert scale questionnaire which was tested for validity and reliability, while data analysis was carried out by simple linear regression using SPSS. Findings - The results showed that curriculum changes had a positive and significant effect on students' learning motivation, with a regression coefficient value of 0.396, a t-value of 5.005, and a significance of 0.000 (<0.05). A determination value (R²) of 0.204 indicates that 20.4% of the variation in learning motivation is influenced by curriculum changes, while the rest by other factors. These results confirm that the implementation of a curriculum that is relevant, contextual, and supported by teacher competence is able to increase students' motivation to learn.]. Originality/Value - This research reinforces the theory of Educational Change Fullan and the ARCS Keller motivational model that educational reform is effective when it involves systemic, psychological, and pedagogical changes.